2018
DOI: 10.1038/s41467-017-02648-0
|View full text |Cite
|
Sign up to set email alerts
|

Medial preoptic area in mice is capable of mediating sexually dimorphic behaviors regardless of gender

Abstract: The medial preoptic area (mPOA) differs between males and females in nearly all species examined to date, including humans. Here, using fiber photometry recordings of Ca2+ transients in freely behaving mice, we show ramping activities in the mPOA that precede and correlate with sexually dimorphic display of male-typical mounting and female-typical pup retrieval. Strikingly, optogenetic stimulation of the mPOA elicits similar display of mounting and pup retrieval in both males and females. Furthermore, by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
192
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(208 citation statements)
references
References 67 publications
13
192
3
Order By: Relevance
“…Recent studies have identified MeA Kiss neurons and the POA as regulators of sexual motivation and behaviour in male rodents [15, 16, 44]. Several studies have identified various neuronal types in the POA as key players in mediating male-typical mating and paternal behaviour including neurons expressing oestrogen receptor alpha [45], progesterone receptor [46], and galanin [47]. Therefore, future studies will be required to identify the exact cellular substrate in the POA responsive to modulation by MeA Kiss neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified MeA Kiss neurons and the POA as regulators of sexual motivation and behaviour in male rodents [15, 16, 44]. Several studies have identified various neuronal types in the POA as key players in mediating male-typical mating and paternal behaviour including neurons expressing oestrogen receptor alpha [45], progesterone receptor [46], and galanin [47]. Therefore, future studies will be required to identify the exact cellular substrate in the POA responsive to modulation by MeA Kiss neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Their presence in males and absence in females due to developmental apoptosis may explain the sexually dimorphic patterns of flies' social behaviors (Kimura et al, 2008). Yet, recent studies in both mice and flies have revealed the existence of latent neural circuitries that encode malelike mating behaviors in the female brain Rezaval et al, 2016;Wei et al, 2018), suggesting a conserved bisexual nature of brain organization and function . In flies, this circuitry consists of the dsx + pC1 cluster of neurons that are also essential for female sexual receptivity (Rezaval et al, 2016;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Male and female mice were group housed (5 animals maximum/per cage) according to the sex. Castration and sham surgery were performed as previously described (Xu et al, 2012; Wei et al, 2018) with animals anesthetized under intraperitoneal (i.p.) injection of ketamine (80 mg/kg) and xylazine (8 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Videos were manually annotated on a frame-by-frame basis using a custom written MATLAB program as previously described (Xu et al, 2012, Wei et al, 2018), by experimenters blinded to the group information. Behaviors were scored according to the following criteria: nose-to-urogenital contact is defined as “sniff”, also known as “chemoinvestigation”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation